PENGGUNAAN PETA KEPENDUDUKAN DIGITAL PADA SISWA YANG BERMOTIVASI BELAJAR TINGGI DAN RENDAH (Eksperimen Pada Siswa Kelas 1 SMPN 40 Surabaya ) (Pendidikan Geografi, 2008)
Abstract : The objective of the research is to study the effect of using population map and learning motivation on students’ knowledge about population. The research was conducted at SMPN 40 Surabaya with n=81 by using an block design system of experiment. The results  of the research are: (1) The students  who have  higher learning motivation and using pop[ulation digital, their mean learning score is higher than the students how use population digital map but low motivation learning motivation (2) There is an interaction effect between the use of population map and learning motivation on students knowledge about population. .